In-silico tool based on Boolean networks and meshless simulations for prediction of reaction and transport mechanisms in the systemic administration of chemotherapeutic drugs. - Fabián Mauricio Vélez Salazar; Iván David Patiño (PLoS ONE)
Using in-house computational tools, this work focuses on investigating how the combination of the electric field magnitude (E), bloodstream velocity (λinl) and pharmaco-kinetic profile (PK) impacts the reaction and transport mechanisms of drug (RTMs) arising in electro-chemotherapeutic treatments. The first step implies retrieving the ratios between extracellular, free intracellular, and bound intracellular concentrations from numerical simulations, employing a meshless code developed, calibrated and validated in a previous work. Subsequently, a Boolean model is developed to determine the presence, interaction and rates of RTMs based on the comparison of the spatio-temporal evolution of the drug concentration ratios, being this the main contribution of the present work to the comprehension of the phenomena involved in the systemic administration of chemotherapeutic drugs in cancer tumors. Different combinations of E (0 kV/m, 46 kV/m, 70 kV/m), λinl (1x10-4m/s, 1x10-3m/s, 1x10-2m/s) and PK (One-short tri-exponential, mono-exponential) are examined. In general, results show that both the presence and relative importance of RTMs can differ between both PKs for a given combination of E and λinl. Additionally, for a given PK, radial uniformity of transmembrane transport rate is aversively affected by the increase of E and λinl, whereas radial homogeneity of association/dissociation rate is monotonously affected only by E. Regarding the axial uniformity of transmembrane transport rate, this is benefited by the increase of λinl and, in a lower extent, by the reduction of E.